Análise de pinturas rupestres do Abrigo do Janelão (Minas Gerais) por microscopia raman - de Faria,Dalva Lúcia A. (2011)
Rock art paintings from Abrigo do Janelão (Minas Gerais, Brazil) were non-destructively investigated by Raman Microscopy, aiming at the identification of materials used, their interaction and degradation. This technique is particularly tailored for heterogeneous samples and allows unequivocal identification of the substances present in the investigated sample. Pigments, were identified together with products of microbiological degradation; no binders were detected. White pigment was identified as calcite (CaCO3), whereas charcoal was used as black, goethite (α-FeOOH) as yellow and hematite (α-Fe2O3) as red. Whewellite (CaC2O4.H2O) and weddelite (CaC2O4.2H2O) were detected and their origin was assigned to degradation products from microbiological activity.